1993
DOI: 10.1016/0264-410x(93)90333-s
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response after influenza immunization with various vaccine doses: a double-blind, placebo-controlled, multi-centre, dose—response study in elderly nursing-home residents and young volunteers

Abstract: The dose effect (0, 10, 20 and 60 I~g)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Published reports show a dose-response relationship for local reactions and, though less pronounced, for systemic reactions (6,8,(16)(17)(18)(19). We controlled possible dose bias by dividing studies with different doses into separate groups.…”
Section: Discussionmentioning
confidence: 99%
“…Published reports show a dose-response relationship for local reactions and, though less pronounced, for systemic reactions (6,8,(16)(17)(18)(19). We controlled possible dose bias by dividing studies with different doses into separate groups.…”
Section: Discussionmentioning
confidence: 99%
“…This variability between serologic studies is well known and has been described earlier. 11,37,42,43 Although the postvaccination HI titer is a valuable surrogate marker for real protection, it may depend on a number of cofactors that are imperfectly controlled by the study design, among others, prevaccination titer and study population characteristics (age; history of previous exposure to natural influenza, especially the effect of the "original antigenic sin" 44 ; health state; etc). The present heterogeneity among serologic studies does not argue against our conclusion that repeated vaccination is not associated with a decrease in effectiveness.…”
Section: Commentmentioning
confidence: 99%
“…As many of the dose and booster trials reported previously had much smaller sample sizes, they may have suffered from a type II error, that may explain the divergence with previous ®ndings concerning high dose in¯uenza vaccines. Several researchers have reported an improvement in antibody levels in the elderly with increasing antigen dose [Arden et al, 1986;Sullivan et al, 1990;Remarque et al, 1993Remarque et al, , 1999, whereas others have failed to do so [Gross et al, 1988;Peters et al, 1988;Palache et al, 1993]. The improvement observed in antibody titers that was achieved by booster vaccination was not con®rmed by previous reports [Gross et al, 1987;Levine et al, 1987].…”
Section: Discussionmentioning
confidence: 92%